Tissue acquisition for diagnosis of biliary strictures using peroral cholangioscopy or endoscopic ultrasound-guided fine-needle aspiration - Lee, Yun Nah; Moon, Jong Ho; Choi, Hyun Jong; Kim, Hee Kyung; Lee, Hyun Woo; Lee, Tae Hoon; Choi, Moon Han; Cha, Sang-Woo; Cho, Young Deok; Park, Sang-Heum (Endoscopy, 2019)
Background Although endoscopic retrograde cholangiopancreatography (ERCP) is a first-line diagnostic modality for suspected malignant biliary stricture (MBS), the diagnostic yield of ERCP-based tissue sampling is insufficient. Peroral cholangioscopy-guided forceps biopsy (POC-FB) and endoscopic ultrasound-guided fine-needle aspiration biopsy (EUS-FNAB) are evolving as reliable diagnostic procedures for inconclusive MBS. This study aimed to evaluate the usefulness of a diagnostic approach using POC-FB or EUS-FNAB according to the stricture location in patients with suspected MBS.Methods Consecutive patients diagnosed with suspected MBS with obstructive jaundice and/or cholangitis were enrolled prospectively. ERCP with transpapillary forceps biopsy (TPB) was performed initially. When malignancy was not confirmed by TPB, POC-FB using a SpyGlass direct visualization system or direct POC using an ultraslim endoscope was performed for proximal strictures, and EUS-FNAB was performed for distal strictures as a follow-up biopsy. Results Among a total of 181 patients, initial TPB showed malignancy in 122 patients, and the diagnostic accuracy of initial TPB was 71.8 % (95 % confidence interval [CI] 65.3 % – 78.4 %]. Of the 59 patients in whom TPB was negative for malignancy, 32 had proximal biliary strictures and underwent successful POC. The remaining 27 patients had distal strictures and underwent successful EUS-FNAB. The accuracy of malignancy detection using POC-FB for proximal biliary strictures and EUS-FNAB for distal biliary strictures was 93.6 % (95 %CI 84.9 %−100 %) and 96.3 % (95 %CI 89.2 %−100 %), respectively. The overall diagnostic accuracy for the combination of TPB with either POC-FB for proximal strictures and EUS-FNAB for distal strictures was 98.3 % (95 %CI 95.9 %−100 %) and 98.4 % (95 %CI 95.3 %−100 %), respectively. Conclusions An approach using POC-FB or EUS-FNAB according to the stricture location may be useful in the diagnosis of suspected MBS.